The effect of anterior disc displacement with polycystic ovarian syndrome on adolescent condylar bone remodeling - Jiali Sun; Chuyao Wang; Jieyun Zhao; Xin Nie; Chuan Lu; Xiang Ye; Dongmei He (BMC Oral Health)
Abstract Background Adolescent females have a high prevalence of temporomandibular joint (TMJ) anterior disc displacement (ADD), which can lead to condylar resorption and dentofacial deformity. Polycystic ovarian syndrome (PCOS) is a common endocrine disorder that disrupts bone metabolism. However, the effects of PCOS on bone remodeling especially after disc repositioning (DR) surgery are not well understood. Materials and methods This was a retrospective study. Patients aged 12 to 20 years diagnosed with ADD were reviewed and matched into 3 groups: A (ADD without PCOS), B (ADD with untreated PCOS), and C (ADD with treated PCOS). Each group was divided into 2 subgroups according to ADD observation (A1, B1, C1) and DR (A2, B2, C2). Condylar height (CH) was measured by MRI at the start (T0) and after more than 6 months follow-up (T1). ∆CH (T1-T0) were compared within and between groups. Results 93 patients (157 joints) with an average age of 15.17 ± 2.35 years and follow-up period of 14.04 ± 9.11 months were selected in the study. ∆CH in Group B1 was significantly larger than that in Groups A1 and C1 (p = 0.048, p = 0.018). While in Group B2, it was significant smaller than Groups A2 and C2 (p < 0.001, p = 0.023). There was no significant difference of ∆CH between Groups C2 and A2. DR acquired larger ∆CH than observation within each A, B, C Groups (p < 0.05). Multiple linear regression analysis showed that ∆CH was related to the presence of PCOS (p = 0.003), PCOS treatment (p < 0.001), and DR (p < 0.001). Conclusions Adolescent ADD with untreated PCOS can aggravate condylar degeneration and affect bone remodeling after DR. PCOS treatment can improve bone remodeling.